2023
DOI: 10.1021/acssuschemeng.3c02691
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Enzymatic Hydrolysis of High-Solids Content Corncobs by a Lytic Polysaccharide Monooxygenase from Podospora anserina S Mat+ for Valuable Monosaccharides

Abstract: Lytic polysaccharide monooxygenase (LPMO) has been found to enhance cellulase activity and promote efficient utilization of corncob cellulose. To this end, a novel LPMO from Podospora anserina S mat+ (PaLPMO) through in silico screening was heterologously expressed in Escherichia coli BL21(DE3) and its biochemical properties were investigated. To reduce production costs, chaperones and site-directed mutagenesis were employed to enhance the protein's solubility, yielding an 8% increase. Through single-factor ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…Nevertheless, in a recent study, Cai and colleagues have shown that an AA9 from P. anserina (enzyme ID not reported) could enhance the absolute glucose extraction yield on corncobs by up to 24% (using 8 mg/g of industrial Cellic CTec3 cocktail and 4 mg/g of LPMO) . Although it is possible that the boost observed in this study directly originates from the action of the tested Pa AA9, it is also likely that this LPMO could act as a H 2 O 2 supplier for the AA9s potentially present in the Cellic CTec3 cocktail (3 AA9s are encoded in the genome of T.…”
Section: Discussionmentioning
confidence: 82%
“…Nevertheless, in a recent study, Cai and colleagues have shown that an AA9 from P. anserina (enzyme ID not reported) could enhance the absolute glucose extraction yield on corncobs by up to 24% (using 8 mg/g of industrial Cellic CTec3 cocktail and 4 mg/g of LPMO) . Although it is possible that the boost observed in this study directly originates from the action of the tested Pa AA9, it is also likely that this LPMO could act as a H 2 O 2 supplier for the AA9s potentially present in the Cellic CTec3 cocktail (3 AA9s are encoded in the genome of T.…”
Section: Discussionmentioning
confidence: 82%